POLITICAL WILL DALAM PENGELOLAAN MASALAH KERUSAKAN ALAT PEMBERI ISYARAT LALU LINTAS DI KOTA PALEMBANG - Aprillah, M.; Ropik, Ainur; Miftafariz Mirza, Ibrahim (PRAJA: Jurnal Ilmiah Pemerintahan, 2026)
Palembang City, as one of the metropolitan cities in Indonesia, experiences high levels of mobility and traffic congestion, making the effectiveness of traffic signal devices (Alat Pemberi Isyarat Lalu Lintas / APILL) crucial for ensuring traffic flow and safety. However, recurring damage to APILL at various locations in Palembang has disrupted traffic movement and increased the risk of traffic accidents. This study aims to analyze the implementation of the local government’s political will through the Palembang City Transportation Agency in managing APILL damage, as well as to identify factors affecting the effectiveness of its management. The study employs a descriptive qualitative approach using a case study method. Data were collected through in-depth interviews, field observations, and documentation review. Data analysis refers to the five dimensions of political will proposed by Brinkerhoff, namely initiative, prioritization, law enforcement, mobilization of support, and sustainability. The findings indicate that the government’s political will has been reflected in the implementation of the SIRUM/ATCS monitoring system, the establishment of repair priority scales, and inter-agency coordination. Nevertheless, the implementation has not been fully optimal due to limited monitoring coverage, inconsistencies in determining repair priorities, and the weak enforcement of standard operating procedures. In addition, the government’s political will tends to be situational and has not yet been fully internalized as a sustainable priority agenda. The main constraints include environmental factors, aging equipment, non-technical damage, limited energy sources, and bureaucratic and coordination challenges. Therefore, strengthening political will on a sustainable basis is necessary to achieve more effective APILL management in supporting traffic safety and flow in Palembang City.